2010
DOI: 10.1007/s11033-010-0459-6
|View full text |Cite
|
Sign up to set email alerts
|

Start codon targeted polymorphism for evaluation of functional genetic variation and relationships in cultivated peanut (Arachis hypogaea L.) genotypes

Abstract: Cultivated peanut possesses an extremely narrow genetic basis. Polymorphism is considerably difficult to identify with the use of conventional biochemical and molecular tools. For the purpose of obtaining considerable DNA polymorphisms and fingerprinting cultivated peanut genotypes in a convenient manner, start codon targeted polymorphism technique was used to study genetic diversity and relatedness among 20 accessions of four major botanical varieties of peanut. Of 36 primers screened, 18 primers could produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(111 citation statements)
references
References 37 publications
6
94
0
Order By: Relevance
“…SCoT is similar to random amplified polymorphic DNA or intersimple sequence repeat, but has some advantages such as being closely linked with the target gene, provides more information correlated with biological traits, and universality in plants compared with random DNA markers. These advantages have been verified in rice (Oryza sativa) (Collard and Mackill, 2009), mango (Mangifera indica) (Luo et al, 2011), peanut (Arachis hypogaea) (Xiong et al, 2011), grape (Vitis vinifera) (Guo et al, 2012), dendrobe (Dendrobium nobile) (Bhattacharyya et al, 2013), and limpograss (Hemarthria altissima) (Huang et al, 2013) for cultivar identification and genetic diversity analysis.…”
Section: Introductionmentioning
confidence: 95%
“…SCoT is similar to random amplified polymorphic DNA or intersimple sequence repeat, but has some advantages such as being closely linked with the target gene, provides more information correlated with biological traits, and universality in plants compared with random DNA markers. These advantages have been verified in rice (Oryza sativa) (Collard and Mackill, 2009), mango (Mangifera indica) (Luo et al, 2011), peanut (Arachis hypogaea) (Xiong et al, 2011), grape (Vitis vinifera) (Guo et al, 2012), dendrobe (Dendrobium nobile) (Bhattacharyya et al, 2013), and limpograss (Hemarthria altissima) (Huang et al, 2013) for cultivar identification and genetic diversity analysis.…”
Section: Introductionmentioning
confidence: 95%
“…Various markers have been used in peanut diversity studies that have shown varying degrees of polymorphism, including AFLP and DAF (6.86 and 21.14%, respectively, He and Prakash, 2001); RAPD (42.73%, Raina et al, 2001);and InDel (33.30%, Liu et al, 2015) ( Table 6). In addition, Xiong et al (2011) found variation in SCoT (38.22%), ISJAP (28.10%), DAMD (36.00%), and SRAP-IAAP (43.15%) markers (Table 6). In these reports, the number of accessions used was smaller than the number (54) of accessions evaluated in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Since the first report indicating that cultivated peanut presents some DNA polymorphism (Kochert et al, 1991), restriction fragment length polymorphism (RFLP) and random amplified polymorphic DNA (RAPD) markers have been employed to construct genetic maps and to dissect the genetic diversity in peanut (Garcia et al, 1995;Burow et al, 2001;Raina et al, 2001). In addition, amplified fragment length polymorphism (AFLP) (He and Prakash, 2001;Herselman, 2003), inter-simple sequence repeat (Raina et al, 2001), sequence related amplified polymorphism (SRAP) , and start codon targeted (SCoT) polymorphism markers (Xiong et al, 2011) have been developed and utilized to study the genetic diversity and relationships in cultivated peanut. Simple sequence repeat (SSR) markers have been widely applied in genetic diversity studies of peanut (Hopkins et al, 1999;He et al, 2003;Ferguson et al, 2004;Barkley et al, 2007;Freitas et al, 2007;Wang et al, 2015), because they are reproducible, simple, and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…This has been validated through study of genetic diversity among rice varieties (Collard & Mackill, 2009b). Further studies have utilized the technique to investigate genetic relationships in a number of plant species (Xiong et al, 2011;Murthy, 2011). These studies show that SCoTs can be used solely, or in combination with other techniques, to assess genetic diversity and to obtain reliable information about population processes and structure across different plant families.…”
Section: Start Codon Targeted (Scot) Polymorphismmentioning
confidence: 99%